Structural basis of asymmetry in the human immunodeficiency virus type 1 reverse transcriptase heterodimer. - Wang, J (1994)
The reverse transcriptase from human immunodeficiency virus type 1 is a heterodimer consisting of one 66-kDa and one 51-kDa subunit. The p66 subunit contains both a polymerase and an RNase H domain; proteolytic cleavage of p66 removes the RNase H domain to yield the p51 subunit. Although the polymerase domain of p66 folds into an open, extended structure containing a large active-site cleft, that of p51 is closed and compact. The connection subdomain, which lies between the polymerase and RNase H active sites in p66, plays a central role in the formation of the reverse transcriptase heterodimer. Extensive and very different intra- and intersubunit contacts are made by the connection subdomains of each of the subunits. Together, contacts between the two connection domains constitute approximately one-third of the total contacts between subunits of the heterodimer. Conversion of an open p66 polymerase domain structure to a closed p51-like structure results in a reduction in solvent-accessible surface area by 1600 A2 and the burying of an extensive hydrophobic surface. Thus, the monomeric forms of both p66 and p51 are proposed to have the same closed structure as seen in the p51 subunit of the heterodimer. The free energy required to convert p66 from a closed p51-like structure to the observed open p66 polymerase domain structure is generated by the burying of a large, predominantly hydrophobic surface area upon formation of the heterodimer. It is likely that the only kind of dimer that can form is an asymmetric one like that seen in the heterodimer structure, since one dimer interaction surface exists only in p51 and the other only in p66. We suggest that both p51 and p66 form asymmetric homodimers that are assembled from one subunit that has assumed the open conformation and one that has the closed structure.